Convergence and Coexistence Among The Schools Of Islamic Law: A Methodology - Habiburrahman, Muhammad (Ar Raniry : International Journal of Islamic Studies, 2016)
Most of the texts of Shari'ah came in the form of fundamental principles and general provisions. The texts are often general and flexible at a large extent, so that it would not be narrowed for the people. In addition, the texts, which encompass the partial and detailed provisions of Shari'ah, are drafted in such a way that can accommodate more than single understanding and particular interpretation. Consequently, this leads to the presence of multiple Schools and standpoints in the Islamic law. Nevertheless, all these Schools of law are right, based on the standard fundamentals, and derived from single source. Yes, these Schools may lead the nation to separation and dispersion if the followers were unaware of the issue of pluralism and ignorant about the reasons of disagreement among the scholars. This study discusses the essence of the Schools of Islamic law (madhahib) elucidating the fundamental nature thereof, and provides mechanisms and methodology to deal with these Schools, ensuring the peaceful coexistence among their followers. It might be understood that the intention here is to try to change the Schools and their stands to make them closer to each other. This is not intended and in fact this is not required. There should be respect for the autonomy of the Schools and their natures and standpoints. However, it is required to ensure that following these Schools is not based on the intolerance towards other Schools, or ignoring them, or attacking them. Rather, it remains within the framework of plurality of views and opinions without abusing the relationship of brotherhood and unity among Muslims. Thus, the aim must be here to work on the approximation among the followers of the Schools. This is because in principle these Schools are close to each other since they should be in accordance with the same fundamentals, while the dispute is limited to the corollaries and particulars. Nevertheless, it is not the aim here to abolish the Schools, or to remove the scholarly disputes, or to merge the Schools with each other, or to find a new School. Last but not least, the study aims to highlight the common features, and to respect the differences within the framework of emphasis on unity of the nation. This is further confirmed in sharing one view by multiple Schools regarding many particulars and subsequent issues. Hence, it is quite common to find single and same opinion that is adopted and advocated by more than one School of Islamic law.